Horizontal Gene Transfer of Antibiotic Resistance from Acinetobacter baylyi to Escherichia coli on Lettuce and Subsequent Antibiotic Resistance Transmission to the Gut Microbiome - Marlène Maeusli (American Society for Microbiology, 2020)
ABSTRACT Agricultural use of antibiotics is recognized by the U.S. Centers for Disease Control and Prevention as a major contributor to antibiotic-resistant infections. While most One Health attention has been on the potential for antibiotic resistance transmission from livestock and contaminated meat products to people, plant foods are fundamental to the food chain for meat eaters and vegetarians alike. We hypothesized that environmental bacteria that colonize plant foods may serve as platforms for the persistence of antibiotic-resistant bacteria and for horizontal gene transfer of antibiotic-resistant genes. Donor Acinetobacter baylyi and recipient Escherichia coli were cocultured in vitro, in planta on lettuce, and in vivo in BALB/c mice. We showed that nonpathogenic, environmental A. baylyi is capable of transferring plasmids conferring antibiotic resistance to E. coli clinical isolates on lettuce leaf discs. Furthermore, transformant E. coli from the in planta assay could then colonize the mouse gut microbiome. The target antibiotic resistance plasmid was identified in mouse feces up to 5 days postinfection. We specifically identified in vivo transfer of the plasmid to resident Klebsiella pneumoniae in the mouse gut. Our findings highlight the potential for environmental bacteria exposed to antibiotics to transmit resistance genes to mammalian pathogens during ingestion of leafy greens. IMPORTANCE Previous efforts have correlated antibiotic-fed livestock and meat products with respective antibiotic resistance genes, but virtually no research has been conducted on the transmission of antibiotic resistance from plant foods to the mammalian gut (C. S. Hölzel, J. L. Tetens, and K. Schwaiger, Pathog Dis 15:671–688, 2018, https://doi.org/10.1089/fpd.2018.2501; C. M. Liu et al., mBio 9:e00470-19, 2018, https://doi.org/10.1128/mBio.00470-18; B. Spellberg et al., NAM Perspectives, 2016, https://doi.org/10.31478/201606d; J. O’Neill, Antimicrobials in agriculture and the environment, 2015; Centers for Disease Control and Prevention, Antibiotic resistance threats in the United States, 2019). Here, we sought to determine if horizontal transmission of antibiotic resistance genes can occur between lettuce and the mammalian gut microbiome, using a mouse model. Furthermore, we have created a new model to study horizontal gene transfer on lettuce leaves using an antibiotic-resistant transformant of A. baylyi (AbzeoR).